STUDY ON TRENDS IN SPORT COMUNICATION - Pomohaci Marcel; Turcu Dionisie (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Everyday life, namely the immediate economic pressures have led sports organizations to use a greater number of communication tools and techniques to increase the visibility of sport, to attract additional funds. Sports communication instruments have a dual completion: obtaining funding and communication.